Passion for Saving Country in Dan Browns Deception Point 2001an Existentialist Approach - Taufika, Muhammad Insan; muhammad, Dr. Phil. Dewi Candraningrum, M.Ed, M.Ed; muhammad, Titis Setyabudi, S.S, M.hum (2016)
This study is aimed to show passion for saving life in Deception point Novel by using existentialist perspective. It is done by establishing two objectives: the first is analyzing the novel based on its structural elements and the second is analyzing the novel based on the Existentialist Perspective. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Deception Point movie written by Dan Brown released in 2001. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, theme, and editing are related to each other and form a unity. Second, based on the Existential analysis, awareness of the meaning of life leads to meaningful action in human's life. Keywords: Passion for saving life, Deception Point, Meaningful Action, Existentialist Perspective.